Sex differentiation in the organization of emergency sensorimotor action - Plokhikh Viktor Volodymyrovych; Yanovska Svitlana Germanivna (Insight: the psychological dimensions of society, 2022)
The purpose of the study is to determine characteristics of the gender factor’s influence on the structure and speed of implementation of emergency sensorimotor action. The empirical research method is a computer-assisted laboratory experiment with an intrasubject implementation plan. The participants were students divided into two groups: 78 men and 74 women. In the series of attempts, the participants completed tasks of simple sensorimotor response, sensorimotor response, and two-choice response. In the two-choice response task, the subject is first given a reference point for the option of future stimulation, to which one should adjust urgently. After, the subject should act when the stimulus appears. The U Mann-Whitney test and Spearman’s Rank correlation coefficient were applied to process experimental data. Results. It is established that men surpassed women in the speed of simple sensorimotor response (U= 2147.00; p=.006) and sensorimotor choice response (U=1733.00; p<.001), and the reaction speed in a twochoice task with one possible stimulus (U=2078.00; p=.003) and three possible stimuli (U=2006.00; p=.001). Сompared to women, men spend less time on organizing emergency sensorimotor action under a rapid change in the current situation (U=2090.00; p=.003). It is found that in the male group, in contrast to the female one, the orientation time in a twochoice task correlates with the time of motor response in the variant with one possible stimulus (r=-.257; p=.023) and anticipation probability (r=.365; p=.001). Conclusions. The general structure of the organization of emergency sensorimotor action does not differ significantly in men and women. The time of simple sensorimotor response and choice reaction in individual tasks and, if required, their emergency selective implementation in a two-choice task is less in the male group than in the female one. Men have a faster organization of emergency sensorimotor action in response to rapid changes in the current situation than women. Compared to men, relative operational complexity for women regarding the differentiation of time references in the anticipation process since stimulus appearance is associated with a destabilization of the speed of sensorimotor action.